BECOMING ADOLESCENT AND BEING MOTHER: SOCIAL REPRESENTATIONS OFADOLESCENTS IN THE POST PARTUM - Dafne Paiva Rodrigues; Francisco Rafael de Araújo Rodrigues; Lucilane Maria Sales da Silva; Maria Salete Bessa Jorge; Léa Dias Gomes Pimentel Vasconcelos (Universidade Federal do Paraná, 2009)
The objective was to apprehend the social representations of adolescents in the post partum period aboutbeing a mother in adolescence. This study was based on the Theory of Social Representation of Moscovici, and wasdeveloped in a public maternity hospital in the municipality of Fortaleza-CE with 25 adolescents in the post partum period,through semi-structured interviews. The construction of social representations about motherhood in adolescence showscontradictory opinions. The most visible contradictions are: being a mother and being a mother in adolescence, in whichthe first shall be designed as a virtue, while the second is stereotyped as prison, through the difficulties faced in developingthe motherhood role. The conclusion is that the maternity in adolescence shows the importance of educational programson sexual health, focusing on the intersectoriality between schools, health services and society to develop mechanismsto identify and intervene with the teenagers at high risk for early motherhood.